Ecofisiologia de espécies de plantas daninhas submetidas a estresse hídrico e à reidratação - Lima, Mayky Francley Pereira de (2015)
There is no doubt that the effect of weed causes damage to various human activities and especially those for agricultural use. Therefore, if not properly handled, can reduce productivity and production quality due to competition for light, nutrients, and especially water, which is the most abundant resource, while the most limiting to agricultural productivity. This study aimed to assess the potential for competition four weed species by water. The experiment was conducted in a factorial 4 x 2, distributed in a randomized complete block design, with five replications. were studied species malva-branca (Waltheria indica L.); crotalária (Crotalaria retusa L.); mussambê (Cleome affinis DC.) and trapoeraba (Commelina benghalensis L.), with two water regimes (with and without water stress). Plants subjected to water stress had suspended irrigation during flowering, and maintained until the CO2 assimilation rate of plants to morning 9am reached values close to zero, at the resumed irrigation. As from the date irrigation suspension the plants were submitted to the following evaluations: water potential before dawn (ΨAM) and water potential at noon (ΨMD) (MPa); photosynthesis (A; CO2 μmol m-2); stomatal conductance (gs; μmol H2O m-2 s-1), and transpiration (E; mmol H2O m-2 s-1) carried out every day until the photosynthetic rates of plants subjected to water stress is to equalize plants without stress. At the end of the experiment was measured leaf area (cm2), the dry mass of roots, stems, leaves and total (g), the chlorophyll content index near the apex of the leaves and the next leaves the base. Was also determined daily water consumption species (mL). The results grouped the plants into two groups: trapoeraba and mussambê, considered conservative, keeping the high water potential and transpiration, being uncompetitive by water, and crotalária and malva-branca, medium investors, able to reduce the water potential and stomatal aperture values higher, resulting in greater potential for competition for water. And in low water availability conditions, the mauve-white is the most competitive for water, because it can maintain high water consumption levels over time